Advances in the potential roles of Cullin-RING ligases in regulating autoimmune diseases - Zhang, Xiaoying; Liu, Yu’e; Zhang, Tong; Tan, Yuying; Dai, Xiangpeng; Yang, Yong-Guang; Zhang, Xiaoling (Frontiers in Immunology, 2023)
Cullin-RING ligases (CRLs) are the largest class of ubiquitin E3 ligases regulating the stability and subsequent activity of enormous important proteins responsible for the development and progression of various diseases, including the autoimmune disease (AIDs). However, the detailed mechanisms for the pathogenesis of AIDs are complicated and involved multiple signaling pathways. The in-depth understanding of the underlying regulating mechanisms for the initiation and progression of AIDs will aid in the development of effective therapeutic strategies. Cullin-RING ligases (CRLs) play critical roles in regulating AIDs partially by affecting the key inflammation-associated pathways such as NF-κB, Jak-STATs and TGF-β. In this review, we summarized and discussed the potential roles of CRLs in inflammation signaling pathways and pathogenesis of AIDs. Furthermore, the advances in the development of novel therapeutic strategies for AIDs through targeting CRLs were also highlighted.